Exercise limitation in chronic kidney disease: An experimental pilot study with leg and arm exercise - Helena Wallin; Eva Jansson; Ragad Said; Sigrid Lundberg; Pourya Zolfaghardidani; Maria J. Eriksson; Anette Rickenlund; Patrik Sundblad (Physiological Reports)
Abstract Maximal oxygen uptake (VO2max) in healthy subjects is primarily limited by systemic oxygen delivery. In chronic kidney disease (CKD), VO2max is potentially reduced by both central and peripheral factors. We aimed to investigate the effect on VO2peak of adding arm exercise to leg exercise. Ten individuals with CKD stages 3–5 and 10 healthy controls, matched for age, sex, body size, and physical activity level, were included. Subjects performed two maximal exercise tests, one with legs only (L exercise) and one test where arm exercise was added to leg exercise (LA exercise). The increase in VO2peak, when comparing LA exercise with L exercise, was significantly higher in CKD (0.20 ± 0.18 L/min or 2.31 ± 1.78 mL/(kg·min)) than in controls (0.019 ± 0.12 L/min or 0.26 ± 1.62 mL/(kg·min); p = 0.02 and 0.01, respectively). The decrease in peak leg workload, when comparing L exercise with LA exercise, was larger in controls than in CKD, in absolute terms (p = 0.002) and relative to body weight (p = 0.01). VO2max in individuals with CKD is dependent on the active muscle mass, supporting a peripheral limitation to VO2max in CKD. By contrast, the control group appeared to have a more central limitation to VO2max.